The Effectiveness of Kahoot Media-Based Physics Learning in the University of Mataram Environment - Anggun Almadani; Nabila Dwi Septia; Luluk Tsaroya Zarkasyi; Nahdatul Wesi; Umratun Hasanah; Gina Fadilla; Muhammad Hardiansyah; Kormil Saputra; Fatima Naimi (Tinta Emas Publisher, 2025)
This study aims to evaluate the effectiveness of quiz media-based physics learning in improving concept understanding, student engagement, and the ability to reflect on the material taught. Through a survey of 41 students at Mataram University, it was found that the majority of students responded positively to the use of quizzes. A total of 65.59% of students agreed that quizzes helped them understand basic physics concepts, while 63.24% felt more involved in learning. However, although most students showed positive perceptions, around 13.24% to 19.12% of students felt that quizzes did not provide significant benefits. This study suggests the use of more adaptive and varied quizzes, as well as continuous evaluation to improve learning effectiveness.